Proximate Analysis and Comparative Evaluation of Antioxidant, Antidiabetic and Antibacterial Activities of Capsicum Species Consumed in Nepal - Kalauni, Surya Kant; Pokhrel, Krishna Prasad; K. C., Anant; Khanal, Lekha Nath (Amrit Journal, 2024)
Chili has been consumed worldwide for a long time and is known for its aroma, hot taste, vibrant color, and its richness in various vitamins, minerals, capsaicin, and carotenoids, which offer protective attributes against health complaints such as rheumatism, joint pain, bronchitis, and cancer. This study aims to conduct a proximate analysis, phytochemical composition, estimation of total phenolic and flavonoid content, and antioxidant, antidiabetic, and antibacterial activities of three commonly used chili species in Nepal. Proximate analysis showed the presence of the highest percentage of crude fiber (16.43%), carbohydrate (13.59%), and fat (1.47%) in Capsicum frutescence. Using the Folin-Ciocalteu reagent method, the phenolic content was found in the range from 71.80 ± 3.36 mg GAE/g in Capsicum frutescens to 6.59 ± 0.50 mg GAE/g in Capsicum annuum var. cerasiforme. Similarly, the total flavonoid content was in the range of 22.38 ± 2.56 mg QE/g in C. frutescens to the minimum of 3.20 ± 0.43 mg QE/g in C. annuum var. annuum. The methanol extract of Capsicum frutescens was found to exhibit significant antioxidant capacity (IC50 = 99.13 ± 3.55 μg/mL). The extract exhibited moderate α-amylase inhibition capacity on evaluation by CNPG3 method but did not show antibacterial activity against both gram negative and Gram-positive bacteria. The results of this study validate the traditional use of chili as nutraceutical and therapeutic purposes.